IMPRESSIVE PENETRATION OF GENDER HABITUS IN AYAO WONIWON, TRADITIONAL PROVERBS OF YAPEN PEOPLE IN SERUI TOWN PAPUA - Aleda Mawene; Wigati Yektiningtyas (Fakultas Sastra Universitas Negeri Malang, 2020)
IMPRESSIVE PENETRATION OF GENDER HABITUS IN AYAO WONIWON, TRADITIONAL PROVERBS OF YAPEN PEOPLE IN SERUI TOWN PAPUA Abstract: Penetration of gender habitus in Ayao Woniwon, Traditional expressions of the Yapen people is carried out through cultural objects. The penetration is impressive which gives suggestions to men and women so that they perceive differences in behavior not as a cultural construction, but as something natural and legitimate. This study used qualitative data. Data collected in the form of symbols of cultural objects that are reflected in the sentence Ayao Woniwon. It was collected by using the technique of observation and deep interview from Yapen people who live in Serui city and its surroundings. The holistic approach was adopted by combining cultural study (form and content model) and literary study (semiotic approach and feminist literary criticism). The researcher found that Ayao Woniwon was created (anonymous) to protect males' roles that were symbolized by Kavi (loincloth), Yawainye (torch), Ayume (sail), Umbaio (wooden fork), and Epane (Nibong floor) and position of females on private-domestic work that was symbolized by Keepo Anane (papeda chopstick), Tewami (fireplace), and Ingkuja (Noken ).The impressive penetration of gender habitus into Ayao Woniwon through these symbols causes gender disposition systems not to be eroded by time but continues to be inherited in the Yapen community.Keywords: Penetration-impressive, Gender habitus, Traditional proverbs, Yapen.PENETRASI IMPRESIF HABITUS GENDER PADA AYAO WONIWON, UNGKAPAN TRADISIONAL MASYARAKAT YAPEN DI KOTA SERUI PAPUAAbstrak: Penetrasi habitus gender pada ayao woniwon, ungkapan tradisional masyarakat Yapen dilakukan melalui benda-benda budaya. Penetrasi tersebut bersifat impresif yang memberi sugesti pada diri laki-laki dan perempuan sehingga mereka menganggap perbedaan perilaku bukan sebagai konstruksi budaya, melainkan sebagai sesuatu yang alamiah dan absah. Kajian dilakukan dalam lingkup paradigma penelitian kualitatif. Datanya berupa simbol benda-benda budaya yang tercermin dalam kalimat ayao woniwon. Data tersebut bersumber pada masyarakat Yapen yang berdomisili di Kota Serui dan sekitarnya. Pengumpulan data dilakukan melalui teknik observasi dan wawancara mendalam. Pendekatan yang digunakan bersifat holistik, yang memadukan studi kultural (Model Analisis Bentuk dan Isi) dan studi sastra (Pendekatan Semiotik dan Kritik Sastra Feminis). Temuan penelitian menunjukkan bahwa ayao woniwon yang diciptakan (anonim) ini memproteksi peran laki-laki yang disimbolkan dengan kavi (cawat), yawainye (obor) ayume (layar) umbaio (garpu kayu), dan epane (lantai nibun) dan memposisikan perempuan pada pekerjaan privat-domestik dengan simbol keepo anane (gata-gata papeda), tewami (tungku), dan ingkuja (noken). Penetrasi impresif habitus gender ke dalam ayao woniwon melalui simbol-simbol tersebut menyebabkan sistem-sistem disposisi gender tidak hilang digerus waktu tetapi terus diwariskan di dalam komunitas masyarakat Yapen.Kata kunci: Penetrasi-impresif, Habitus gender, Ungkapan tradisional, Yapen.